Spontaneous rupture of splenic artery aneurysm in the course of pregnancy: maternal-fetal survival and normal delivery at term - Perdomo, Roberto; Cuadro, José C; Falconi, Luis M (Cirugía del Uruguay, 1976)
A case is presented of a spontaneous rupture of a .splenic artery aneurysm in early pregnancy. It seems to be the second case reported with maternal and fetal surviva! after the rupture. Comments are made on the diagnostic and therapeutic problems pose by this rare and serious abdominal emergency. Particular emphasis is placed on the importance of its knowledge, in order to improve its prognosis.